THU0480 Multicenter, prospective, controlled double-blind study comparing FIB-19-01, a phytotherapy treatment for fibromyalgia, to a dietary supplement and to conventional treatment in patients suffering from fibromyalgia. (15th June 2017) - Bertin, P; Baron, D; Barmaki, M; Russ, I; Maindet-Dominici, C; Fardellone, P; Ginies, P; Conrozier, T; Nizard, J
Abstract : Background: Current therapeutic modalities for fibromyalgia syndrome (FMS) do not provide satisfactory results to a high percentage of patients and new approaches have to be explored. Objectives: This randomised, double-blind, controlled study was aimed to assess the efficacy and safety of adding a new treatment of herbal medicine, specifically developed to improve the quality of life of patients with FMS (Fib-19–01), to the current therapeutic regimen. Methods: In this double-blind, placebo-controlled study, females with FMS, insufficiently improved by their current treatments, were randomised in one of the 3 following arms: Patients of arm 1 received Fib-19–01, 1 tablet twice a day. Those of arm 2 received a food supplement claimed to have analgesic properties (FSAP), in a double-blind way, and patients of arm 3 continued the previous treatment. without adding anything else (NoT). All continued the conventional treatment throughout the 6 months of follow-up. Inclusion criteria: women suffering from FMS (ACR criteria) with a Fibromyalgia Index Questionnaire FIQ >46. The primary endpoint was the change in FIQ score between baseline (Day 0) and month 6 (M6). Secondary Criteria included variation between D0 and M6 of the following scores: Pichot scale, Pittsburgh Sleep Quality Index (PSQI) index, SF-12 mental and social, SF-12 physical, HAD scales for depression and anxiety. Statistical analysis: Comparison intra-group (D0-M6) and intergroup on the ITT population. Results: The ITT and per protocol populations were constituted of 101 and 75 patients. They were not statistically different and were in accordance with that expected (age 49, BMI 25, high percentage of antidepressant and anticonvulsant treatments). FIQ decrease throughout the follow-up was significant only in the Fib-19–01 group; (p<0.001). In intergroup comparison, improvement was higher for Fib-19–01 (-13.5) than in the 2 other groups (-5.4 and -5.6) but the difference did not reach statistical significance (p=0.08). Analysis of variance in repeated measurements of FIQ showed a significant difference between Fib-19–01 and FSAP (p=0.03). On the secondary criteria, only Fib-19–01 patients were improved for PICHOT scale (p<0.001), PQSI (p=0.02), SF12 mental and social (p<0.001), HAD anxiety (p=0.003) and depression (p=0.004). In intergroup comparison Fib-19–01 was superior to FSAP for Pichot scale (p=0.013), mental and social SF12 (p=0.018), HAD depression (p=0.013). No significant difference was found between FSAP and NoT groups. Therefore, in this study FSAP acts as a placebo which gives the results of this study a level of evidence I. All treatments were well and similarly tolerated. Conclusions: A 6-month treatment with Fib-19–01 improved all FMS scores excepted the physical SF 12, as opposed to FSAP and conventional treatment alone, which did not significantly improve any. This study showed that Fib-19–01 has a therapeutic effect in the FMS chiefly on the components "fatigue", "emotion and social life" and "depression" of the disease, without safety concern. Disclosure of Interest: P. BERTIN: None declared, D. BARON: None declared, M. BARMAKI: None declared, I. RUSS: None declared, C. MAINDET-DOMINICI: None declared, P. FARDELLONE: None declared, P. GINIES: None declared, T. CONROZIER Consultant for: LABRHA SAS, J. NIZARD: None declared